Strategies for Improving Employee Performance through the Enhancement of Personality, Trust, and Job Satisfaction: An Empirical Study on Operational Employees of PT Lintas Buana Taksi - Wibowo, Hendra Ratno; Yusnita, Nancy; Hadiyat, Yayan (Asosiasi Ahli Administrasi Indonesia, 2025)
This study examines strategies to enhance employee performance through the roles of personality, trust, and job satisfaction among operational employees of PT. Lintas Buana Taksi (Blue Bird Group). The research was motivated by the gap between operational targets and actual outcomes during 2021–2023, including high accident claims, increasing customer complaints, and suboptimal performance indicators in quality, quantity, effectiveness, and efficiency. These conditions highlight the significance of psychological and behavioral factors in shaping performance. The objective of this study is to analyze the direct effect of personality on performance and to assess the mediating roles of trust and job satisfaction. A quantitative survey method was applied, using questionnaires distributed to operational employees. Data were analyzed through Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results show that personality does not directly affect performance significantly; however, it has a strong positive influence on trust and job satisfaction. Furthermore, both trust and job satisfaction positively and significantly affect employee performance. Mediation analysis confirms that personality indirectly improves performance through trust and job satisfaction. These findings indicate that employee performance enhancement is more effective when personality traits are supported by a trusted work environment and higher job satisfaction. The study contributes theoretically by enriching organizational behavior and human resource management literature, and practically by offering insights for management. Personality-based recruitment, trust-building initiatives, and improvement of job satisfaction are recommended strategies to achieve sustainable employee performance in the transportation service industry.